Primary hypertrophic osteoarthropathy - E. L. Trisvetova (Научно-практическая ревматология)
The article presents information about a rare hereditary disease – primary hypertrophic osteoarthropathy with autosomal dominant and autosomal recessive inheritance. Genetic heterogeneity is responsible for the clinical polymorphism of symptoms that appear in childhood and adolescence. Differential diagnosis should be carried out with secondary hypertrophic osteoarthropathy, which occurs in 90% of cases and is associated with malignant neoplasms, rheumatic diseases and other diseases. X-ray signs are of great importance to clarify the localization, extent and nature of bone lesions. There is no specific treatment for the disease.